DEVELOPMENT OF 2D ANIMATION MEDIA AND CREATIVE SUPPORTING MEDIA FOR BASIC ENGLISH LEARNING FOR ELEMENTARY SCHOOL STUDENTS - I Komang Putra; Leli Ramdan (Yayasan Sinergi Widya Nusantara, 2025)
Purpose: Basic English learning in elementary schools still largely uses conventional methods such as textbooks and oral explanations from teachers, making it less engaging for students and not fully suited to the learning characteristics of early childhood, which require visual and contextual media. This study aims to design 2D animation media to support basic English learning for third-grade elementary school students, specifically for the Merdeka Curriculum Unit 7